Effectiveness of a spiritual adaptation of cognitive behavioural therapy in improving resilience, self‐esteem and spirituality among clients with opioid use disorder: A quasi‐experimental study - Sonbol, Hassan Mohammed; Metwally El‐Sayed, Mona; Taha, Samah Mohamed; Abdelwahab Khedr, Mahmoud; El‐Ashry, Ayman Mohamed; Abd Elhay, Eman Sameh (Journal of psychiatric and mental health nursing, 2025)
Accessible Summary What is known on the subject? Opioid use disorder (OUD) is a prevalent problem among Egyptian youth, and achieving recovery and abstinence is challenging. Cognitive behavioural therapy (CBT), a well‐known approach, can be particularly beneficial when it addresses psychological aspects such as resilience and self‐esteem. What does the paper add to existing knowledge? Our research is recognized as a trailblazer in integrating a spiritual adaptation of CBT with spiritual elements for treating patients with OUD in the Egyptian context. This innovative approach marks a significant advancement in the field. The study found a statistically significant increase in the mean scores of resilience, self‐esteem, and spirituality (p < .001 each) following the spiritual adaptation of CBT sessions compared to the control group. What are the implications for practice? The findings can guide psychiatrists and nurses in providing more comprehensive and effective care to patients with OUD by incorporating a spiritual adaptation of CBT with spiritual components into treatment plans. Introduction Opioid use disorder (OUD) is a prevalent problem among Egyptian youth, and achieving recovery and abstinence is challenging. Cognitive behavioural therapy (CBT), a well‐known approach, can be particularly beneficial when it addresses psychological aspects such as resilience, self‐esteem and spirituality. Aim This study aimed to evaluate the effectiveness of a spiritual adaptation of CBT in enhancing these factors among clients with OUD. Methods A quasi‐experimental study with a control group was conducted using a pretest‐posttest design. The study included 49 clients with OUD and 46 clients in the control group. The Rosenberg Self‐Esteem Scale–Modified Arabic Version, Daily Spiritual Experience Scale, and the Connor–Davidson Resilience Scale were used as measurement tools. CBT was delivered in 60‐min group sessions. After 3 months, the questionnaires were re‐administered to evaluate the effectiveness of a spiritual adaptation of CBT sessions. Results The study found a statistically significant increase in the mean scores of resilience, self‐esteem and spirituality (p < .001 each) following a spiritual adaptation of CBT sessions compared to the control group. Discussion A spiritual adaptation of CBT effectively enhanced resilience, self‐esteem and spirituality in clients with OUD. Implications for Practice Understanding the effectiveness of a spiritual adaptation of CBT in enhancing resilience, self‐esteem and spirituality can enable psychiatrists and nurses to provide more comprehensive and effective care to patients with OUD.